Qualidade do leite de vacas criadas no sistema silvipastoril no Vale do Cauca, Colômbia - Bolaños, Carmen A.d. [UNESP] (2014)
The silvopastoral system is characterized by increasing the production of milk with a greater number of cows per hectare due to the higher amount of protein in the diet. In silvopastoral system cows are fed in addition to pasture, small trees and shrubs. The aim of this study was determinate the main indicators of milk quality and mastitis causal agents in cows bred on silvopastoral system. We evaluated the composition (fat, total protein, lactose, solids, dry extract, nonfat dry and urea nitrogen), somatic cell count (SCC), total bacterial count (TBC), occurrence of clinical and subclinical mastitis, microbiological isolation, in vitro antimicrobial sensitivity profile and detection of antimicrobial residues in milk produced by 100 cows raised in silvopastoral systems, as well as the bulk tank and churns in farms of Cauca Valley, Colombia. The concentration of the major constituents of milk were 3.24% fat, 3.27% total protein, 4.40% lactose, 10.62% dry extract, 8.57% nonfat dry and 15.82mg/dL urea nitrogen, while the bulk tank and churns was 3.51% fat, 3.20% total protein, 4.34% lactose, 11.72% dry extract, 8.47% nonfat dry and 14.57mg/dL urea nitrogen. The cell count of the cows and the bulk tank was 141,252.75 CS/mL and 363,078.05 CS/mL respectively. The TBC mean in cows and the bulk tank was 4,466.84 CFU/mL and 24,547.01 CFU/mL respectively. The main microorganisms isolated from the udder cows were Corynebacterium bovis, Staphylococcus aureus, Staphylococcus hyicus, Staphylococcus spp., Streptococcus dysgalatiae, while the bulk tank were identified more often Streptococcus spp., Enterobacter cloacae, Hafnia alveii, hemolytic Streptococcus and Streptococcus spp. Antimicrobial residues in cow milk and bulk or churn were detected in 30% and 86% respectively. The silvopastoral system showed to be good alternative to milk production in cow. However is important the care with antimicrobial residues in milk and the analysis of all quality parameters to ensure a differentiated product.